The health situation of precarious settlements: the case of the Manuel Bustos Settlement in Viña del Mar - Morgado, Gabriela; Zenteno, Elizabeth; Viveros, Francisca; González, Camila; Rodríguez, Paula; Zamora, Catalina (Revista Chilena de Salud Pública, 2018)
Objective: To explore the health status of members of the Manuel Bustos Settlement, in the region of Valparaiso, in terms of socioeconomic and environmental characteristics and their selfperceived health status. Material y Methods: A descriptive and non-experimental quantitative study was conducted. A questionnaire was applied through semi-structured interviews to 89 families in the settlement. Results: Families of the settlement are characterized principally by their young age, for attending regular health appointments (mainly the Well Child check ups and preventative annual physical exam for adults), and, in the case of the majority, for being enrolled in a local community health center. Their houses have irregular human waste disposal and 40% of households have a member with hypertension. On average, the residents valued their health status with a grade of 5, on a scale from 1 to 7. Conclusions: The health situation of the inhabitants of the settlement presents positive aspects related to health center enrollment and regular attendance of controls. However, the high prevalence of hypertension, the precarious conditions of eliminating human waste, and the presence of nearby landfills are risk factors for health that must be addressed by government and non-governmental organizations, which work in this territory.